PENGARUH PENGALAMAN PENGGUNA, KUALITAS PRODUK, PERSEPSI HARGA, DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE FACEBOOK DI KOTA DENPASAR - Ni Putu Cempaka Dharmadewi; Putu Elmo Setyawan (Jurnal Bakti Saraswati (JBS), 2025)
This study aims to examine the influence of user experience, product quality, price perception, and consumer trust on purchasing decisions in the Facebook marketplace. The study was conducted in Denpasar, which has the largest population of Facebook marketplace users in Bali. The sample used in this study consisted of 120 respondents selected using the purposive sampling method. Data collection was carried out thru the distribution of questionnaires, and data analysis was performed using multiple linear regression to test the relationship between independent and dependent variables. The research results indicate that user experience has a positive and significant influence on purchase decisions, where the better the user experience, the higher the purchase decisions they make. Product quality also has a positive and significant influence on purchasing decisions, with higher quality products leading to increased purchasing decisions. Additionally, price perception has a positive and significant influence on purchasing decisions, with fair price perceptions increasing purchasing decisions. Consumer trust also has a positive and significant influence on purchasing decisions, indicating that high trust in the Facebook marketplace can drive purchasing decisions. Based on these findings, this study suggests that businesses on the Facebook marketplace should focus more on improving user experience, maintaining product quality, setting competitive prices, and building consumer trust to drive increased purchasing decisions